Evaluation of International Mergers and Acquisitions through a case study- Garanti Bank, Turkey - Karabudak, Zeynep Berfu (2009)
The aim of this dissertation is to study the process of cross-border mergers and acquisitions (M&As). This is achieved by understanding the general concept of mergers and acquisitions and then considering case study of Garanti Bank (a Turkish bank) which is an example of a successful international M&A. Due to increased globalisation, the world has witnessed an increasing trend in international M&As, however the success rates are not high. Therefore, through analysing the Garanti Bank acquisition, this study aims to evaluate the process of international M&A and identify the factors which play a vital role in its success. To achieve this objective, the existing research on the process of M&As is reviewed in depth, starting with pre-M&A issues like driving factors for M&A decisions and continuing with post-M&A issues like company performance. This study concludes with the reasons behind the successes or failures of such initiatives. The knowledge constructed through the literature review is used in the discussion of the case study, where both primary and secondary data are used for analysing the acquisition. The analysis is based on semi-structured interviews (primary data) and data collected from newspapers, press releases and company web pages (secondary data), in order to illustrate and clarify the processes underlying Garanti Bank’s acquisition. This research concludes with the key differences in the acquisition process that make the case of Garanti Bank a success.